(untitled) (Journal of Veterinary Medicine and Animal Production, 2023)
This study was conducted to evaluate effects of modifying the traditional grazing practices on desert ewes reproductive performance and lamb growth in North Kordofan State, Sudan. Eighty ewes were divided into four groups with similar weight and age, and assigned randomly to four differed in management patterns. The groups were: GDW5 group (control) managed to emulate the traditional local practice; where the animals were grazed in morning and evening periods, kept under trees’ shade at noon and watered every 5 days. GNW3 group, animals were grazed in the nighttime kept under shade in the daytime and had watered every 3 days. GNW1 group, animals were grazed in the nighttime, kept under shade in the daytime and water access every 1 day. (GNW1+S) group, animals were grazed in the nighttime; kept under shade in the daytime, watered every day, and supplemented with concentrated. During the breeding season, all ewes were allowed to mate with rams. Lambs born were weaned after 4 months. Then raised for 2 months, during which lambs of each group was managed similar to their dams. The results showed that pregnancy and lambing rates were 85% in GDW5 group (traditional management), increased significantly to 95% in GNW3 group, and to 100% in GNW1 and GNW1+S groups. The litter size also increased from 1.0 in GDW5 group to 1.10, 1.05 and 1.45 for GNW3, GNW1 and GNW1+S groups, respectively with significant differences among the different groups. Lamb loss percentage was 25% in GDW5 group and decreased significantly to 5% in GNW3 and GNW1 groups, and to 0 % in GNW1+S group. Birth, weaning, and final weights were significantly affected by management pattern. GNW3, GNW1 and GNW1+S groups had 30.5%, 39.1%, and 73.9%, respectively heavier birth weight than the control group. The weaning weight increased by 28.9%, 34.4%, and 43.6 % in GNW3, GNW1 and GNW1+S respectively, compared to that of the control group. Whereas, the increment in final weight was 21.1%, 25.7%, and 30.0% for GNW3, GNW1 and GNW1+S respectively, compared to control group. In conclusion, sheep night grazing with water access within short intervals improved reproductive performance, decreased lamb’s mortality rate and increased birth and weaning weights. Night grazing and daily watering sheep plus supplementation had dramatically effects in increasing in the number of litter size, birth and weaning weights and reduced mortality rate. Lambs after weaning can maintain good growth performance without supplementation when a high-quality pasture was available.